2007
DOI: 10.1128/jvi.02844-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hepatitis B Virus (HBV)-Specific T-Cell Dysfunction in Chronic HBV Infection

Abstract: Dysfunctional CD8؉ T cells present in chronic virus infections can express programmed death 1 (PD-1) molecules, and the inhibition of the engagement of PD-1 with its ligand (PD-L1) has been reported to enhance the antiviral function of these T cells. We took advantage of the wide fluctuations in levels of viremia which are typical of chronic hepatitis B virus (HBV) infection to comprehensively analyze the impact of prolonged exposure to different virus quantities on virus-specific T-cell dysfunction and on its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
731
6
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 804 publications
(780 citation statements)
references
References 34 publications
38
731
6
5
Order By: Relevance
“…The independent effect of the length of HBV DNA suppression on specific immune response, found in this study, was partly in accordance with previous studies (16,17). It is widely hypothesized that the T-cell function exhaustion of CHB patients occurs because of the prolonged exposure of T cells to high quantities of viral antigens and that T-cell resting from antigenic stimulation is a crucial requirement for restoration of a functional antiviral T-cell response (3,5,9,18). In this study, the results demonstrated a negative correlation between HBV-DNA levels and HBV-specific CTL responses in untreated CHB patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The independent effect of the length of HBV DNA suppression on specific immune response, found in this study, was partly in accordance with previous studies (16,17). It is widely hypothesized that the T-cell function exhaustion of CHB patients occurs because of the prolonged exposure of T cells to high quantities of viral antigens and that T-cell resting from antigenic stimulation is a crucial requirement for restoration of a functional antiviral T-cell response (3,5,9,18). In this study, the results demonstrated a negative correlation between HBV-DNA levels and HBV-specific CTL responses in untreated CHB patients.…”
Section: Discussionsupporting
confidence: 92%
“…The permanent suppression of HBV replication following treatment requires a robust acquired immune response against the HBV core and envelope antigens (5). There is evidence that antiviral therapy alters the balance between host immunity and viral replication, enabling weakened virus-specific immune responses to strengthen, broaden, and possibly control the infection, probably due to the decreased HBV antigen levels allowing the recovery of the T-cell response (6)(7)(8)(9). This mechanism may be important in contributing to complete recovery from CHB.…”
Section: Introductionmentioning
confidence: 99%
“…6,39,40 We made a similar observation when incubating total splenocytes isolated from wild-type (WT), but not PD-L1 knockout (KO) mice with anti-PD-L1 antibody (Figure 3a; compare lanes 1–2 and 3–4 in Figure 3b), thus demonstrating antibody specificity. However, co-culture of WT splenocytes with WT adipocytes significantly dampened the anti-PD-L1 antibody effect on CD8 + IFNγ + T cells (compare lanes 1–2 and 5–6 in Figure 3b).…”
Section: Resultsmentioning
confidence: 56%
“…5 Increasing evidence demonstrates that upregulation of the PD-1 inhibitory receptor mediates HIV-specific CD8 1 T-cell functional exhaustion and CD8 1 T cell is apoptosis-sensitive, resulting in an impairment of CD8 1 T cell's ability to control virus replication. [6][7][8][9] Involvement of the PD-1 pathway has also been shown during hepatitis B and C virus infection [10][11][12][13] with PD-L1 expression demonstrated in situ on a wide variety of solid tumors including pancreas, lung, ovarian and bladder tumors. [14][15][16][17][18] Studies relating PD-L1 expression on tumors to disease outcome show that PD-L1 expression strongly correlates with unfavorable prognosis in kidney, bladder, gastric and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 95%